2001
DOI: 10.1074/jbc.m105769200
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Desmosomal Proteins in Apoptotic Cells

Abstract: Activation of caspases results in the disruption of structural and signaling networks in apoptotic cells. Recent biochemical and cell biological studies have shown that components of the cadherin-catenin adhesion complex in epithelial adherens junctions are targeted by caspases during apoptosis. In epithelial cells, desmosomes represent a second type of anchoring junctions mediating strong cell-cell contacts. Using antibodies directed against a set of desmosomal proteins, we show that desmosomes are proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 44 publications
4
97
0
Order By: Relevance
“…46,90 In turn, caspase activation leads to proteolytic cleavage of numerous intracellular targets, including CSP, which upregulates calpain activity, 91 and the adhesion molecules desmogleins, desmocollins, and ␤-and ␥-catenins. [92][93][94] The extracellular domains of desmoglein 3 and desmocollin 3 are released from the cell surface by a metalloproteinase activity, because in the presence of caspase and/or metalloproteinase inhibitors, both cleavage reactions are almost completely inhibited. This may initiate or augment production autoantibodies to desmoglein 3 and other adhesion molecules found in PV patients (reviewed by Grando 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…46,90 In turn, caspase activation leads to proteolytic cleavage of numerous intracellular targets, including CSP, which upregulates calpain activity, 91 and the adhesion molecules desmogleins, desmocollins, and ␤-and ␥-catenins. [92][93][94] The extracellular domains of desmoglein 3 and desmocollin 3 are released from the cell surface by a metalloproteinase activity, because in the presence of caspase and/or metalloproteinase inhibitors, both cleavage reactions are almost completely inhibited. This may initiate or augment production autoantibodies to desmoglein 3 and other adhesion molecules found in PV patients (reviewed by Grando 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the anti-occludin antibody is directed against the Cterminus of occludin the apparent molecular mass of fragment 2 suggested that it is generated by cleavage within the first extracellular loop of occludin. Therefore, we assumed that, similar to the apoptotic cleavage of cadherin extracellular domains (Herren et al, 1998;Steinhusen et al, 2001;Weiske et al, 2001), occludin is cleaved by metalloproteinase(s) in the extracellular loop. To address this question cells were preincubated with metalloproteinase inhibitors before induction of apoptosis.…”
Section: Caspase-and Metalloproteinase-mediated Cleavage Of Occludinmentioning
confidence: 99%
“…Preparation of Cell Lysate and Western Blot AnalysisHint1-transfected cells were lysed 72 h after transfection, and 50 g of total protein was analyzed by SDS-PAGE and subsequent Western blotting as described previously (38). For immunodetection, antibodies were diluted in TST (anti-Bax, 1 g/ml; anti-Bcl-2, 0.5 g/ml; anti-PARP, 1:2000; anti-p53, 1 g/ml;…”
Section: Methodsmentioning
confidence: 99%